Electronic bookstore / Choy Wai Yin - Choy , Wai Yin (2001)
The e-Bookstore is a web application of electronic commerce which simulates an electronic bookstore. This project will complement the traditional way of doing business in a bookstore. The University Bookstore in the University of Malaya will be the target client for this Project. The e-Bookstore will enable university students and lecturers to have a more pleasant book shopping experience by leveraging on the benefits of the Internet to provide a virtual bookstore on the World Wide Web. Users of the web site will be able to conduct basic book shopping activities like book browsing, book searching, online ordering and placing orders for books currently physically unavailable in the University Bookstore. Besides, the application will also enable the bookstore owner to understand the business heller and to respond quickly to customers' needs As an example, accurate and concise reports can be obtained easily whilst newsletters can be sent directly to the customers via electronic mail. It is envisioned that the e-Bookstore will benefit the everyday users of the bookstore by saving considerable costs in terms of transportation, time and effort will also benefit the bookstore owner by providing up to date information on the business and its inventory system besides introducing latest Information Technology solutions for the business. It ts hoped that this project will demonstrate the benefits of conducting business via The internet. Hopefully, it will serve as a platform whereby University of Malaya will lead the way in achieving some of the aspirations outlined in Vision 2020.